Hydraulic gates and valves in free surface flow and submerged outlets - Lewin, Jack (Thomas Telford, 2001)
Providing a comprehensive overview of hydraulic gates and valves, this 2nd ed. clearly describes the principle options available to engineers and designers. The main advantages and disadvantages of all hydraulic gates and valves are outlined, highlighting potential problems in their use.